2009
DOI: 10.1111/j.1742-7843.2008.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

SMND‐309, a Novel Derivate of Salvianolic Acid B, Attenuates Apoptosis and Ameliorates Mitochondrial Energy Metabolism in Rat Cortical Neurons

Abstract: SMND-309, a novel compound (2E)-2-{6-[(E)-2-carboxyvinyl]-2,3-dihydroxyphenyl}-3-(3,4-dihydroxyphenyl) acrylic acid, is a new derivate of salvianolic acid B. The present study elucidates the effects of SMND-309 on the cultured rat cortical neuron damage induced by oxygen-glucose deprivation. The results show that SMND-309 treatment obviously attenuates apoptosis and ameliorates mitochondrial energy metabolism in rat cortical neurons by increasing cell survival rate, mitochondrial antioxidant enzyme activities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The main pharmacological activities of Sal B include inhibition of lipopolysaccharide (LPS)‐inducible COX‐2 in human aortic smooth muscle cells (HASMCs) via JNK and ERK suppression,17 reduction of MMP‐2 and MMP‐9 in cholesterol‐fed mice and LPS‐stimulated HASMCs,18 reduction of leucocyte adhesion to human aortic endothelial cells (HAECs)19 and attenuation of ischaemia–reperfusion injury 20, 21. Additionally, administration of Sal B resulted in an improvement in regional cerebral blood flow in the ischaemic cerebral hemisphere in rats,20, 22 attenuation of apoptosis in rat cortical neurons23 and neuroprotection in cerebral ischaemia 24. Furthermore, Sal B has also been shown to protect endothelial cells from oxidative stress,25 to inhibit TGF‐β1‐induced myofibroblast transition and restore epithelial morphology26 and to inhibit platelet aggregation and adhesion under flow conditions 27…”
Section: Introductionmentioning
confidence: 99%
“…The main pharmacological activities of Sal B include inhibition of lipopolysaccharide (LPS)‐inducible COX‐2 in human aortic smooth muscle cells (HASMCs) via JNK and ERK suppression,17 reduction of MMP‐2 and MMP‐9 in cholesterol‐fed mice and LPS‐stimulated HASMCs,18 reduction of leucocyte adhesion to human aortic endothelial cells (HAECs)19 and attenuation of ischaemia–reperfusion injury 20, 21. Additionally, administration of Sal B resulted in an improvement in regional cerebral blood flow in the ischaemic cerebral hemisphere in rats,20, 22 attenuation of apoptosis in rat cortical neurons23 and neuroprotection in cerebral ischaemia 24. Furthermore, Sal B has also been shown to protect endothelial cells from oxidative stress,25 to inhibit TGF‐β1‐induced myofibroblast transition and restore epithelial morphology26 and to inhibit platelet aggregation and adhesion under flow conditions 27…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that SalB is effective in inhibiting hepatocellular apoptosis by regulating apoptotic-related factors in the mitochondrial death pathway. SalB is also involved in ameliorating mitochondrial energy metabolism 9 10 . In living cells, mitochondria are relevant sources of reactive oxygen species.…”
mentioning
confidence: 99%
“…A summary of in vitro effects that attributes to the potential therapeutic effects of salvianolic acid derivatives are shown in Table 1 [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. By assessing the β-secretase (β-site amyloid precursor protein (APP) cleaving enzyme or BACE1) and γ-secretase inhibitory activity, a selective effect against BACE1 was demonstrated for SA-B [ 32 ].…”
Section: Salvianolic Acids and Dementiamentioning
confidence: 99%